PENGEMBANGAN E-LKPD TERINTEGRASI PROBLEM BASED LEARNING, UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KETRAMPILAN PROSES SAINS SISWA - Elys Susana; Dede Nuraida; Imas Cintamulya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Critical thinking skills and science process skills are an important part of 21st century competencies that must be possessed by students. One of the efforts that can be done to improve these abilities is by utilizing learning media designed in accordance with the right learning model. This study aimed at developing E-LKPD integrated with the Problem Based Learning model, to improve students' critical thinking skills and science process skills. The research was development research using the Plomp model, through the stages of initial investigation, design in the form of E-LKPD based on the Live Worksheet Platform, so that it was interactive and can be accessed online. The research on this E-LKPD was carried out through validity, practicality, and effectiveness tests. The results showed that the E-LKPD integrated with Problem Based Learning has a high level of validity both material validity and media validity. The effectiveness test is proven to improve critical thinking skills and science process skills. Thus, The E-LKPD is suitable to be used as learning media in teaching science in junior high school.